A character study - Bennett, Hulda (My University, 1908)
Introduction: The nineteenth century has given us two truly great women, -- one of the great authoress who call herself George Eliot is perhaps chiefly known as a novelist, but she is certainly more than a novelist in the sense in which the work applies to writers of great genius.
Citation: Bennett, Hulda. A character study. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: George Eliot; Poetry; Authors; English Literature; Graduating theses; Senior theses; Theses